Role of Kynurenine Pathway in Oxidative Stress during Neurodegenerative Disorders - Mor, Adrian (Cells, 2021)
Neurodegenerative disorders are chronic and life-threatening conditions negatively affecting the quality of patients’ lives. They often have a genetic background, but oxidative stress and mitochondrial damage seem to be at least partly responsible for their development. Recent reports indicate that the activation of the kynurenine pathway (KP), caused by an activation of proinflammatory factors accompanying neurodegenerative processes, leads to the accumulation of its neuroactive and pro-oxidative metabolites. This leads to an increase in the oxidative stress level, which increases mitochondrial damage, and disrupts the cellular energy metabolism. This significantly reduces viability and impairs the proper functioning of central nervous system cells and may aggravate symptoms of many psychiatric and neurodegenerative disorders. This suggests that the modulation of KP activity could be effective in alleviating these symptoms. Numerous reports indicate that tryptophan supplementation, inhibition of KP enzymes, and administration or analogs of KP metabolites show promising results in the management of neurodegenerative disorders in animal models. This review gathers and systematizes the knowledge concerning the role of metabolites and enzymes of the KP in the development of oxidative damage within brain cells during neurodegenerative disorders and potential strategies that could reduce the severity of this process.